Changes in Acylglycerols Composition, Quality Characteristics and In vivo Effects of Dietary Pumpkin Seed Oil upon Thermal Oxidation - Zeb, Alam; Ahmad, Sultan (Frontiers in Chemistry, 2017)
This study was aimed to determine the acylglycerols composition, quality characteristics and protective role of dietary pumpkin seed oil in rabbits. Pumpkin seed oil was thermally oxidized and analyzed for quality characteristics and acylglycerols composition using reversed phase high performance liquid chromatography with diode array detection (HPLC-DAD). Oxidized and un-oxidized oil samples were fed to the rabbits in different doses for two weeks. The changes in the serum biochemistry, hematology, and liver histology were studied. The levels of quality parameters such peroxide value (PV), anisidine value (AV), total phenolic contents (TPC), thiobarbituric acid reactive substances (TBARS), conjugated dienes (CD) and conjugated trienes (CT) significantly increased with thermal treatment. HPLC analyses revealed ten individual triacylglycerols (TAGs), total di-acylglycerols (DAGs), mono-acylglycerols (MAGs), and total oxidized TAGs. Trilinolein (LLL), 1-oleoyl-2,3-dilinolinoyl glycerol (OLL), triolein (OOO) and 1,2-distearoyl-3-palmitoyl glycerol (SSP) were present in higher amounts and decreased with thermal treatment. Animal’s studies showed that oxidized oils decreased the whole body weight, which was ameliorated by the co-administration of un-oxidized oils. The levels of serum biochemical parameters were improved by co-administration of pumpkin seed oils. There were no significant effects of both oxidized and un-oxidized pumpkin seed oil on the hematological and histological parameters of rabbits. In conclusion, nutritionally important triacylglycerols were present in pumpkin seed oil with protective role against the toxicity of its corresponding oxidized oils.